DETERMINAN KEPUTUSAN PEMBELIAN PARFUM LOCAL BRAND (STUDI PADA WANITA BALI) - Aghivirwiati, Gusti Ayu; Wiwik Purnamayanti, Ida Ayu Gede; Suarjaya, I Kadek Dwi; Dharma Saputra, I Putu Andika; Mira Dwijayanti, Ni Kadek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025, 2025)
This research examines the impact of trust in local brands and perceived value on purchasing decisions for local brand perfumes among Balinese women. The study is significant due to the rapid growth of Indonesia's local perfume industry, driven by rising consumer awareness of products that reflect cultural identity and sustainability. The study focuses on understanding the unique preferences of Balinese women, who have distinct tastes related to scent, aesthetics, and cultural values. Using a quantitative approach with a survey and Partial Least Squares Structural Equation Modeling (PLS-SEM), the research found that trust in local brands and perceived value significantly influence purchasing decisions. Trust was found to have a substantial positive impact on perceived value, which in turn strongly influenced buying behavior. Based on these findings, the study recommends that local perfume brands focus on strengthening consumer trust, enhancing educational campaigns about product benefits, and emphasizing their cultural and sustainable values to improve marketing strategies and increase consumer loyalty.